Investigation the financial risk contagion between Iran and selected financial partners - Habib Ansari Samani; Hadis Heydarpoor (مدلسازی اقتصادسنجی, 2019)
The purpose of this study is to study the financial interactions between financial markets of selected financial partner of Iran, including China, France, Germany, Italy and the UAE. For this purpose, the VAR model has been used. Financial risk data is collected annually (from 1984 to 2017). The results indicated that there was a positive and two-side relationship between the financial risk fluctuations between Iran and China, the UAE and Italy, the United Arab Emirates and China during the period under review. In addition, financial risk aversion was observed one- side from Iran to Italy and the UAE to France and China to the UAE. Also, financial risk aversion from Germany to China, Iran, Italy, and the United Arab Emirates was seen one-side, in other cases, there was not Fluctuation overflow. Ultimately, it could be said that Germany was only country affected by risk of the other countries.